2005
DOI: 10.1097/01.mlg.0000154744.71184.c7
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Radical Surgery and Postoperative Radiotherapy for Squamous Carcinoma of the Temporal Bone

Abstract: The overall disease-free survival for the entire series was 43.2%. Node-positive disease, poorly differentiated squamous cell histological findings, brain involvement, and salvage surgery were associated with a poorer outcome. The improved survival (66%) of patients treated de novo in the study series compared with those treated with salvage surgery (33%) suggested that early referral and aggressive primary surgical treatment with postoperative radiotherapy offer the greatest chance of cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
134
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(144 citation statements)
references
References 21 publications
8
134
0
2
Order By: Relevance
“…It is important to note that other studies have demonstrated anecdotal numbers of long-term survivors with brain invasion from advanced SCC after temporal bone resection. 10 Hence, resection in this situation cannot be uniformly recommended. Rather, a case-by-case evaluation of the patient's palliative goals is necessary.…”
Section: Surgical Factors Affecting Pfs and Osmentioning
confidence: 99%
“…It is important to note that other studies have demonstrated anecdotal numbers of long-term survivors with brain invasion from advanced SCC after temporal bone resection. 10 Hence, resection in this situation cannot be uniformly recommended. Rather, a case-by-case evaluation of the patient's palliative goals is necessary.…”
Section: Surgical Factors Affecting Pfs and Osmentioning
confidence: 99%
“…Early surgical attempts to remove these tumors usually involved high morbidity and mortality. These mortality rates have substantially decreased from Lewis's 8 series to the more recent series of Moffat et al and Yin et al [7] as a result of advances in surgery and radiotherapy in the last three decades. The overall 5-year survival rates rank between 40 and 70%, but only reach 20% when advanced stages are considered.…”
Section: Discussionmentioning
confidence: 98%
“…Surgical resection is crucial as a treatment modality, and early surgical intervention is associated with increased survival [2,9,27].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the management has evolved from piecemeal temporal bone resection to en bloc temporal bone resection and further to combined modality treatment of surgery and post-operative RT [9]. In a retrospective analysis of 21 patients, Kollert et al [29] found that stage-dependent lateral or subtotal TBR (write full for first time) combined with parotidectomy as well as a neck dissection was the most beneficial approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation